Pengaruh Perbedaan Konsentrasi Gliserol dalam Susu Skim Kuning Telur untuk Proses Penyimpanan Sperma Beku terhadap Motilitas dan Viabilitas Spermatozoa Ikan Patin (Pangasius pangasius) [Effect Of Different Glycerol Concentration In Skim Milk And Egg Yolk Diluter For Storage Process Of Frozen Semen On Sperm Motility And Viability Of Catfish (Pangasius pangasius)] - Sudarno Sudarno; Bagus Rizki Novianto; Endang Dewi Masithah (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Needs of catfish seed always increase every years, especially for farming activities. Fulfillment demand of seed in large quntities and continuing are the main obstacle in the production process of catfish. This can be overcome by the process of cryopreservation. This process requires diluents and cryoprotectants to maintain the fertility of spermatozoa. Skim milk and egg yolks diluents has been used on fish because it was applied to carp and showing a good result of sperm motility and fertilization rate. Glycerol as cryoprotectant was reported effective to be used for European Catfish than the other kind cryoprotectant. This study aimed to determine the effect of different concentrations of glycerol in the diluent skim milk and egg yolk on the motility and viability of catfish (Pangasius pangasius) spermatozoa after freezing. This research method is the experiment with completely randomized design (CRD) as the experimental design. The treatment used is different glycerol concentrations, P1 (11%), P2 (13%), P3 (15%), and P4 (17%) and each of the treatment was repeated 5 times. The main parameters measured were motility (%) and viability (%) of spermatozoa. Supporting parameters include odor, color, pH, viscosity, sperm concentration and catfish (Pangasius pangasius). Analysis of the data using Analysis Of Variance (ANOVA) and to determine the best treatment performed Duncan's Multiple Range Test with 95% confidance interval. The results showed that the effect of the concentration of glycerol in the diluent skim milk and egg yolk was not significantly (P> 0.05) on the motility and viability of catfish (Pangasius pangasius) spermatozoa after freezing. Further testing needs to be done on the level of fertility of frozen sperm, as well as the growth rate of seeds produced from sperm frozen catfish (Pangasius pangasius) products